Intermediate Filament Protein BFSP1 Maintains Oocyte Asymmetric Division by Modulating Spindle Length - Yu Li; Hanwen Zhang; Wenjun Zeng; Yilong Miao; Shaochen Sun; Yu Zhang; Bo Xiong (Advanced Science)
Abstract The cytoskeleton is composed of microtubules, microfilaments, and intermediate filaments in cells. While the functions of microtubules and microfilaments have been well elucidated, the roles of intermediate filaments and associated proteins remain largely unknown, especially in meiosis. BFSP1 is an intermediate filament protein mainly expressed in the eye lens to play important roles in the development of congenital cataract. Here, we document that BFSP1 functions as a spindle regulator to drive the oocyte asymmetric division. Specifically, we found that BFSP1 distributed on the spindle apparatus during oocyte meiotic maturation. Depletion of BFSP1 resulted in symmetric division of oocytes, accompanied by the formation of elongated spindles at metaphase I and anaphase/telophase I stages. In addition, immunoprecipitation combined with mass spectrometry analysis identified MAP1B, a microtubule‐associated protein, as an interacting partner of BFSP1. Depletion or mutation of MAP1B phenocopied the meiotic defects observed in BFSP1‐depleted oocytes, and expression of exogenous MAP1B‐EGFP in BFSP1‐depleted oocytes recovered the spindle length and asymmetric division. We further determined that BFSP1 recruited molecular chaperone HSP90α on the spindle to stabilize MAP1B, thereby controlling the spindle length. To sum up, our findings reveal a unique meiotic role for BFSP1 in the regulation of spindle dynamics and oocyte asymmetric division.